Risk Factors of Invasive Fungal Infection in Recipients After Liver Transplantation: A Systematic Review and Meta-Analysis - Liu, Min; Zhu, Zhijun; Sun, Liying (Frontiers in Medicine, 2021)
Objectives: Invasive fungal infection (IFI) remains an important cause of mortality in liver transplantation (LT). The objective of this meta-analysis was to identify the risk factors for IFI after LT. Methods: We searched for relevant studies published up to June 2020 from PubMed, Web of Science, Embase, and the Cochrane Library. Odds ratios (ORs) and their corresponding 95% CIs were used to identify significant differences in the risk factors. Heterogeneity between studies was evaluated by the I2 test, and potential publication bias was assessed with Egger's test. The quality of included studies was evaluated with the Newcastle-Ottawa Scale (NOS). Results: A total of 14 studies enrolling 4,284 recipients were included in the meta-analysis. Reoperation (OR = 2.18, 95% CI: 1.61–2.94), posttransplantation dialysis (OR = 2.03, 95% CI: 1.52–2.72), bacterial infection (OR = 1.81, 95% CI: 1.33–2.46), live donor (OR = 1.78, 95% CI: 1.20–2.63), retransplantation (OR = 2.45, 95% CI: 1.54–3.89), and fungal colonization (OR = 2.60, 95% CI: 1.99–3.42) were associated with the risk factors of IFI after LT. Conclusions: Despite some risk factors that have been identified as significant factors for IFI post-LT, which may inform prevention recommendations, rigorous and well-designed studies with adequate sample sizes should be conducted to solve the limitations of this study.